The morpho-physiological and gene expression of East Timor’s local rice plant (Oryza sativa) response to drought and salinity stress - GREGORIO QUINTAO; MOHAMMAD UBAIDILLAH; SRI HARTATIK; RENDRYANA AULIA NUR KHOFIFA; TRI AGUS SISWOYO (Society for Indonesian Biodiversity, 2023)
Abstract. Quintao G, Ubaidillah M, Hartatik S, Khofifa RAN, Siswoyo TA. 2023. The morpho-physiological and gene expression of East Timor’s local rice plant (Oryza sativa) response to drought and salinity stress. Biodiversitas 24: 4548-4556. East Timor is rich in local rice varieties, such as Silaun, Ime Buci, Me Klan, Me Likan, Me Meak, Me Taek, and Umak Klete. These varieties are tolerant to drought and salinity stress. These superior characteristics emerge as the coping strategy of the rice plants toward environmental conditions such as mountainous, upland planting areas without irrigation networks and coastal regions with high salinity levels. This study determined the tolerance response of East Timor's local rice to drought and salinity stresses. This study was designed in a Completely Randomized Design (CRD) with two factors. The first factor, i.e., rice varieties, consisted of 8 varieties, i.e., Silaun (V1), Ime Buci (V2), Me Klan (V3), Me Likan (V4), Me Meak (V5), Me Taek (V6), Umak Klete (V7), and IR-64 (V8) and the second factor was the abiotic stress treatments, namely no treatment or control (P0), 10% PEG treatment (P1), and 150 mM NaCl treatment (P2). The parameters observed were morpho-physiology and biochemical characteristics of the plants. The results showed that the Silaun local rice variety from East Timor was tolerant to drought and salinity, supported by the gene expressions for tolerance to drought and salinity stress.